HIV subtype-specific gp140-CD4 binding, Temsavir efficacy, and identification of novel adhesion inhibitors against Chinese HIV strains - Liu, Tianyang; Li, Xiaowen; Yang, Xiaolin; Zhang, Shengjie; Wang, Yao; Zhang, Siwei; Cheng, Lin; Tang, Shanshan; Wang, Fuxiang; Zhao, Yao; Lu, Hongzhou; Wei, Lanlan (Frontiers in Immunology, 2025)
IntroductionThe HIV epidemic in China is characterized by significant genetic diversity with multiple circulating recombinant forms (CRFs). The gp120-CD4 interaction, essential for viral cellular entry, exhibits subtype-dependent structural variations that compromise therapeutic efficacy. Although temsavir remains the only FDA-approved adhesion inhibitor, its activity against predominant HIV subtypes in China has not been systematically evaluated.MethodsHIV subtyping of 472 clinical samples identified five major strains (B, CRF01_AE, CRF07_BC, CRF08_BC, and CRF55_01B). Recombinant gp140 proteins from these subtypes were expressed, purified, and analyzed via bio-layer interferometry (BLI) to characterize CD4 binding properties. Structural analyses compared hydrogen bonding and interface buried surface areas. Temsavir’s inhibitory efficacy was assessed, and virtual screening of 13,819 compounds combined with BLI validation was performed to identify novel inhibitors.ResultsSubtype B demonstrated the strongest CD4 binding affinity (KD=79 pM), while CRF55_01B showed the weakest binding (KD=8.76 nM). CRF variants exhibited reduced hydrogen bonding and smaller interface buried surface areas, correlating with diminished binding affinity. Temsavir inhibition was subtype-dependent, achieving 35.7% inhibition for subtype B versus <1.3% for CRF01_AE and CRF55_01B, primarily due to steric hindrance induced by the S375H mutation. Five novel inhibitors targeting CRF55_01B were identified with inhibition rates 19%.DiscussionThis study elucidates the molecular mechanisms of HIV-1 adhesion variation and provides specific candidate HIV adhesion inhibitors for prevalent CRF subtypes in China. Subsequent efforts will focus on preclinical validation and structure–activity relationship optimization of these candidates, laying the groundwork for developing personalized therapeutic strategies against region-specific strains.